Cerebrospinal fluid biomarkers measured by Elecsys assays compared to amyloid imaging. Issue 11 (1st March 2018) - Schindler, Suzanne E.; Gray, Julia D.; Gordon, Brian A.; Xiong, Chengjie; Batrla‐Utermann, Richard; Quan, Marian; Wahl, Simone; Benzinger, Tammie L.S.; Holtzman, David M.; Morris, John C.; Fagan, Anne M.
Abstract: Introduction: Levels of amyloid β peptide 42 (Aβ42), total tau, and phosphorylated tau‐181 are well‐established cerebrospinal fluid (CSF) biomarkers of Alzheimer's disease, but variability in manual plate‐based assays has limited their use. We examined the relationship between CSF biomarkers, as measured by a novel automated immunoassay platform, and amyloid positron emission tomography. Methods: CSF samples from 200 individuals underwent separate analysis for Aβ42, total tau, and phosphorylated tau‐181 with automated Roche Elecsys assays. Aβ40 was measured with a commercial plate‐based assay. Positron emission tomography with Pittsburgh Compound B was performed less than 1 year from CSF collection. Results: Ratios of CSF biomarkers (total tau/Aβ42, phosphorylated tau‐181/Aβ42, and Aβ42/Aβ40) best discriminated Pittsburgh Compound B–positive from Pittsburgh Compound B–negative individuals. Discussion: CSF biomarkers and amyloid positron emission tomography reflect different aspects of Alzheimer's disease brain pathology, and therefore, less‐than‐perfect correspondence is expected. Automated assays are likely to increase the utility of CSF biomarkers.